Special issue of Psyecology: social norms and environmental behaviour - Demarque, C. (2018)
In recent years there have been growing expectations from policymakers towards social sciences in order to reach sustainability goals. Research on social norms is often used to promote changes in pro-environmental behaviour. However, the underlying social psychological mechanisms that explain those changes are not yet well described. This special issue puts together four papers that, from different perspectives, contribute to innovation in this field, proposing theoretically relevant mediators and contextual moderators.